Comparative Historical Sociology of Restaurations - Noreika, Alvydas (Problemos, 2025)
The review discusses the theoretical and methodological presuppostions of Zenonas Norkus' monograph "The Great Restoration" (2023), its contributions to comparative historical sociology and the theory of international law, and provides critical remarks on the methodology used.
Keywords: Zenonas Norkus; Post-communist transformation; Restauration; Revolution